2022
DOI: 10.3390/ijerph191811598
|View full text |Cite
|
Sign up to set email alerts
|

Association between Air Pollution and Squamous Cell Lung Cancer in South-Eastern Poland

Abstract: Air pollution is closely associated with the development of respiratory illness. The aim of the present study was to assess the relationship between long-term exposure to PM2.5, PM10, NO2, and SO2 pollution and the incidence of lung cancer in the squamous subtype in south-eastern Poland from the years 2004 to 2014. We collected data of 4237 patients with squamous cell lung cancer and the level of selected pollutants. To investigate the relationship between the level of concentrations of pollutants and the plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The available data underline the relationship between smoking and air pollution and the risk of lung cancer [ 14 18 ]. Also, in Poland lung cancer incidences and air pollution are linked [ 19 ], especially that according to the World Bank Group, Polish cities remain 36 of 50 of the most polluted urban areas of the European Union [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The available data underline the relationship between smoking and air pollution and the risk of lung cancer [ 14 18 ]. Also, in Poland lung cancer incidences and air pollution are linked [ 19 ], especially that according to the World Bank Group, Polish cities remain 36 of 50 of the most polluted urban areas of the European Union [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed nitrogen dioxide to be a lung cancer carcinogen. Once NO 2 is mixed with the other outdoor air pollution, it becomes more persistent in terms of explaining the appearance of cancers and could constitute the main cause of SCC [ 11 ]. For the cohort of men under the age of 75, the risk ratio was less than 1 in the case of NO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the latter, the risk is far less than the risk caused by smoking, but some researchers estimate that, worldwide, approximately five percent of all lung cancer deaths may be caused by outdoor air pollution [ 4 ]. There is scientific evidence of an increased incidence of respiratory, circulatory and cancer diseases due to exposure to various air pollutants, mainly to particles PM10, PM2.5 and their constituents [ 5 , 6 , 7 , 8 ] as well as to nitrogen dioxide (NO 2 ) [ 9 , 10 , 11 ] or sulphur dioxide (SO 2 ) [ 5 , 12 ]. Exogenous carbon monoxide (CO) is produced by the incomplete combustion of carbon-containing molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the role of H2S gas and SO2 and their association with lung cancer, especially in individuals chronically exposed to these gases [8]. A study in Southeast Poland showed that long-term exposure to SO2 and NO2 gases played a role in increasing the incidence of squamous cell lung cancer [11]. Similarly, an epidemiology study in China found that exposure to air polluted with SO2 was signi cantly associated with an increased incidence of lung cancer [10].…”
Section: Tumormentioning
confidence: 99%